2015
DOI: 10.1126/science.aab2160
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and laser control of attosecond charge migration in ionized iodoacetylene

Abstract: Electronic movement flashing into view Numerous chemical processes begin with ionization: the ejection of an electron from a molecule. What happens in the immediate aftermath of that event? Kraus et al. explored this question in iodoacetylene by detecting and analyzing the spectrum of emitted high harmonics (see the Perspective by Ueda). They traced the migration of the residual positively charged hole along the molecular axis on a time scale faster than a quadril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
521
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 552 publications
(577 citation statements)
references
References 101 publications
17
521
1
2
Order By: Relevance
“…High-harmonic generation from a linearly polarized driver is sensitive to inversion symmetry, the breaking of which leads to emission of even harmonics [15,16] that characterize the time-dependent electronic asymmetry of the studied sample [14,17]. In this Letter, we generalize the sensitivity of HHS to rotational symmetries of atoms and molecules and their time-dependent breaking by introducing bicircular HHS (BHHS), driven by a circularly polarized fundamental field of frequency ω and its counterrotating second harmonic 2ω.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High-harmonic generation from a linearly polarized driver is sensitive to inversion symmetry, the breaking of which leads to emission of even harmonics [15,16] that characterize the time-dependent electronic asymmetry of the studied sample [14,17]. In this Letter, we generalize the sensitivity of HHS to rotational symmetries of atoms and molecules and their time-dependent breaking by introducing bicircular HHS (BHHS), driven by a circularly polarized fundamental field of frequency ω and its counterrotating second harmonic 2ω.…”
mentioning
confidence: 99%
“…Whereas the potential of high-harmonic spectroscopy (HHS) to probe the structure and dynamics of matter on the subfemtosecond and subangstrom scales has been well established [7][8][9][10][11][12][13][14], its ability to probe the symmetry of the medium on these time and length scales has not been addressed. High-harmonic generation from a linearly polarized driver is sensitive to inversion symmetry, the breaking of which leads to emission of even harmonics [15,16] that characterize the time-dependent electronic asymmetry of the studied sample [14,17].…”
mentioning
confidence: 99%
“…One example of such dynamics which garnered considerable attention in recent years is molecular charge migration [5], in which, following ionization, the electrons in a molecular ion undergo a coherent spatial oscillation, driven entirely by electron correlations. Wörner et al identified high-harmonic spectroscopy as a promising tool for studying charge migration, with initial experiments in iodoacetylene [6]. There is not, however, a widely accepted paradigm for how dynamical processes, such as charge migration, manifest in attosecond measurement techniques such as HHS.…”
Section: Introductionmentioning
confidence: 99%
“…HHG is the most dominating method for producing attosecond pulses [9]. HHG has also been used to probe orbital structure [10][11][12][13] and electronic [14,15] and nuclear motion [16][17][18][19]. Furthermore, multi-orbital [13,20,21] and electronic correlation effects [11,22,23] can play an important role and in turn can be studied with HHG and other strong-field processes.…”
Section: Introductionmentioning
confidence: 99%